Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5334/aogh.2878
|View full text |Cite
|
Sign up to set email alerts
|

Practices and Perspectives of Traditional Bone Setters in Northern Tanzania

Abstract: Background: Traditional health practitioners remain a critical source of care in Tanzania, more than 50% of Tanzanians frequently using their services. With a severe shortage of orthopaedic surgeons (1:3.3 million Tanzanians) traditional bone setters (TBSs) could potentially expand access to musculoskeletal care and improve outcomes for morbidity as a result of trauma. Objective: We sought to identify the advantages and disadvantages of traditional bone setting in Tanzania and to assess potential for collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Centralising care for patients with musculoskeletal infection may facilitate MDT working and has been recommended in some high resource settings ( 59 ) but comes at a significant cost to patients, who in low resource settings already face catastrophic out-of-pocket costs. Low resource settings may have specific considerations around community involvement and the role of traditional medicine and ‘bone setters’ ( 60 ).…”
Section: Resultsmentioning
confidence: 99%
“…Centralising care for patients with musculoskeletal infection may facilitate MDT working and has been recommended in some high resource settings ( 59 ) but comes at a significant cost to patients, who in low resource settings already face catastrophic out-of-pocket costs. Low resource settings may have specific considerations around community involvement and the role of traditional medicine and ‘bone setters’ ( 60 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is lower than the studies done in Kano, Nigeria, which was 60.5% [ 14 ] and Northern region of Ghana, 65.7% [ 15 ]. On the other hand, it is higher than the studies done in Tanzania 6.3% [ 16 ], rural areas of Nigeria, 25.6% [ 17 ] and in Ilorin, north central Nigeria, 28.7% [ 9 ]. This difference could be due to the differences in the study setting, and socio-demographic characteristics of study participants in which Ethiopia is less developed than those listed settings.…”
Section: Discussionmentioning
confidence: 82%
“…A study in Kenya also indicated that the cheaper fees requested by TBS increase the belief and reliance on treatment by TBS practitioners [14]. In addition, the possibility of a payment in the form of a kind such as cloth and animals could be another driving force [15][16][17][18]. Bamboo splinting, massaging, splinting by homemade materials, and application of herbal medicines were the commonly used practices for the treatment of fracture by TBS.…”
Section: Discussionmentioning
confidence: 99%
“…Bamboo splinting, massaging, splinting by homemade materials, and application of herbal medicines were the commonly used practices for the treatment of fracture by TBS. ese practices are also implemented by other African countries such as Sudan [6], Nigeria [15], Tanzania [17], and Ghana [19]. Twenty-eight percent of the patients were delayed to get treatment from the hospital due to difficulty to reach care, that is, lack of transportation.…”
Section: Discussionmentioning
confidence: 99%